Introduction: The Year 2000 and the Deaths of Three Who Made Labour History - Palmer, Bryan D. (Labour / Le Travail, 2001)
The study of he working class and commitment to its causes is central to what this journal is about. Three men who made significant contributions to working class life over the course of the last century, but whose personal efforts, sadly and to our collective loss, came to an end in the year 2000, merit our attention. Marcel Pepin, a vibrant voice in the modern history of Quebec's union movement and former leader of the Confederation of National Trade Unions (CNTU/CSN), died 6 March 2000. ...On 15 June 2000 another advocate of Canadian workers, especially those incarcerated in homelessness and poverty, Norman N. Feltes, died. ...Jack Scott was a revolutionary of the 20th century who had hope for the 21st. He no doubt understood, however, that others would be making history in the new millennium, and his contributions had already been made. He died as the century closed, on 30 December 2000.